Growth : Now and Forever? - Ho, Giang (IMF Working Papers; Working Paper ;, 2014)
Forecasters often predict continued rapid economic growth into the medium and long term for countries that have recently experienced strong growth. Using long-term forecasts of economic growth from the IMF/World Bank staff Debt Sustainability Analyses for a panel of countries, we show that the baseline forecasts are more optimistic than warranted by past international growth experience. Further, by comparing the IMF's World Economic Outlook forecasts with actual growth outcomes, we show that optimism bias is greater the longer the forecast horizon.